2004
DOI: 10.1016/s0958-9465(03)00085-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the type and amount of polypropylene fibres for preventing the spalling of lightweight concrete subjected to hydrocarbon fire

Abstract: This paper presents the results from an experimental study on the optimum amount of polypropylene fibres to be used in lightweight high-strength concrete to prevent spalling when exposed to hydrocarbon fire, taking into consideration the characteristics of the lightweight aggregate, the water-to-cement ratio (W/C) of the mixtures, and the length and thickness of the fibres.Twelve different concrete mixtures were made. One block, 610x425x770 mm in size, was cast from each mixture and tested for fire resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
88
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(93 citation statements)
references
References 2 publications
3
88
0
2
Order By: Relevance
“…Spalling occurred above 500 • C for the mixtures NVC and SCC 1 and destroyed some cylindrical specimens. It was observed that relative splitting tensile strength f ct (T)/f ct (20) was reduced up to 300 • C following a similar path for all concretes. Among concrete mixtures tested, SCC2 and SCC5 were more susceptible in reducing their relative splitting tensile strength about 14-18%, at temperatures up to 300 • C. The other concretes presented a slight strength loss ranging from 3 to 9%.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Spalling occurred above 500 • C for the mixtures NVC and SCC 1 and destroyed some cylindrical specimens. It was observed that relative splitting tensile strength f ct (T)/f ct (20) was reduced up to 300 • C following a similar path for all concretes. Among concrete mixtures tested, SCC2 and SCC5 were more susceptible in reducing their relative splitting tensile strength about 14-18%, at temperatures up to 300 • C. The other concretes presented a slight strength loss ranging from 3 to 9%.…”
Section: Resultsmentioning
confidence: 76%
“…A lot of research has been carried out in order to model the spalling tendency of HPC and to propose some alternative solutions such as different mixture proportions or use of materials that provide a passive or active protection against spalling. Among the solutions proposed, the addition of polypropylene fibres seems to be an effective one (15)(16)(17)(18)(19)(20). It was reported (21) that polypropylene melts at 160-168 • C whereas HPC spalls when the air temperature ranges between 190-250 • C.…”
Section: Introductionmentioning
confidence: 99%
“…LWAC has been known offers various advantages due to its lower density [1], higher ratio of strength/weight [2], less conductivity thermal [3,4], better durability properties [5,6], fire resistance [7] and etc. The use of lightweight concrete reduce the size of columns, beams, wall and foundation which as well reducing the dead load and minimizing the damages of structures due to earthquake [8].…”
Section: Introductionmentioning
confidence: 99%
“…Authors [11][12][13] have shown that the behavior of concrete at high temperature can be improved by adding polypropylene fibres (with a ratio varying from 0.5 kg/m 3 -3 kg/m 3 ). The melting (160 o C-170 o C) and vaporization (350 o C) of polypropylene fibres generates not only new pores, but also creates microcracks at the tip of fibres connecting the already existing pores [14]. Ozawa and Morimoto [15] carried out permeability tests on high strength concretes (72 MPa) including 0.15% by volume of PPF.…”
Section: Introductionmentioning
confidence: 99%